Analisis dalam Meningkatkan Pendapatan Masyarakat Desa Naga Kesiangan Melalui Pemasaran Sosial Media - Nurasyah Nurasyah; Adilla Putri; Devi Nirmala; Farhan Hidayat; Intan Purnama S; Putri Dwi Anjani (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
Broomsticks have many benefits, one of which is that they are used in everyday life, for example for household needs, offices or cleaning staff. The broom sticks that are usually used as cleaning tools are made from palm tree frond sticks, coconut frond sticks or you can also use sugar palm sticks, but most people use palm frond sticks and coconut sticks. Naga Kesiangan Village is an agricultural village. So the economic output of the residents and the livelihood of most of the residents are farmers. Of the total number of families (945 families), approximately 672 families (76%) are farmers. The remaining 273 families are civil servants, TNI/Polri, traders, plantation employees and others. Judging from the average income level, the people of Naga Kesiangan Village are classified as poor. The manufacture of broom sticks must be further improved to advance the community's economy. With social media promotional media, people can sell products more widely, not only local people can buy broomstick products.